Long-term evaluation of atmospheric composition reanalyses from CAMS, TCR-2, and MERRA-2 over South Korea: Insights into applications, implications, and limitations. (1st February 2021) - Ryu, Young-Hee; Min, Seung-Ki
Abstract: A 16-year (2003–2018) evaluation of CO, NO2, SO2, O3, and PM10 from three reanalysis products (CAMS, TCR-2, and MERRA-2) against independent observations and intercomparison among reanalyses are performed over South Korea. All three reanalyses show significant and persistent biases in the five pollutants, but the reanalyses partly capture decreasing trends in CO, NO2, SO2, and PM10 and increasing trends in O3 over the 16-year period. CAMS outperforms TCR-2 and MERRA-2 in terms of area-averaged climatology and trends of all species except for SO2 . SO2 is best reproduced in TCR-2. The long-term averaged spatial distributions of the pollutants in CAMS reveal that their spatial distributions are largely influenced by a priori emissions. All reanalysis products show larger biases in CO, NO2, and SO2 in cold months than in warm months. The average daily correlations between bias-corrected reanalysis data and observations are found to be reasonably high for some species: 0.74–0.82 for CO, NO2, and PM10 in CAMS, 0.66 for SO2 in TCR-2, and 0.7 for PM10 in MERRA-2. Although TCR-2 generally shows lower daily correlations than CAMS, it shows the potential that correction of emissions through data assimilation can improve its performance at seasonal and interannual time scales. It is recommended that a bias correction be applied to the reanalysis products for use in regional air quality modeling as initial/boundary conditions or in other relevant studies because each reanalysis product has persistent biases throughout season/year. The evaluation of vertical profiles during KORUS-AQ campaign indicates that CAMS reasonably captures CO, SO2, O3, and aerosols but underestimates NO2 . Highlights: CAMS generally outperforms TCR-2 and MERRA-2 in capturing trends and daily variations. Bias correction is recommended for use in regional air quality modeling. CAMS vertical profiles show reasonable agreements for the pollutants except for NO2 .